The Association between the Levels of Phosphodiesterase 9, Insulin-like peptide 5 and Obesity in Women - Hussein, Zuhair Assi; Majeed, Maysaa Jalal; Al-Anbari, Lubna Amer; Al‐Naqeeb, Suzan Adil Rashid (AL-Kindy College Medical Journal, 2024)
Background: The obesity epidemic is affecting worldwide health, increasing the risk of cardiovascular diseases such hypertension, diabetes, dyslipidemia, and nonalcoholic fatty liver disease. this gave an impetus to study the new variables Insulin-like peptide 5, Phosphodiesterase 9 and their relationship as a cause or effect factors Objective: To validate any associations between Phosphodiesterase 9 (PDE9) and, Insulin-like peptide 5 (INSL5), specific factors and obesity, and to explore how they might integrate with other established agents to combat obesity and improve metabolism. Subjects and Methods: The study was based analytical cross-sectional research was conducted from (February 2022) to (August 2022). The study based on apparently healthy women (primary analyses were made, their blood sugar and lipid profile with the normal reference range) 50 women with age range (20 – 40) years. Fasting blood samples were collected from all the participants in this study, (5 ml) was poured in plane tubes and sera were separated by centrifuging the samples for 10 minutes at 3000rpm for the biochemical and hormonal investigations, therefore they were divided into two group: -first group: consisted of twenty-five obese women without previously diagnosed diseases (BMI>30 kg/m2) . second group: consisted of twenty-five women with normal BMI (BMI= 24.9-18.5 kg/m2). Results: Serum insulin-like peptide 5 showed significant increase in obese women without previously diagnosed diseases (16.31±3.88 µIU/ml), in comparison with women with normal BMI (11.17±3.88 µIU/ml). Serum PDE-9A significantly ((P≤ 0.05) decrease in obese women (6.77±1.95ng/ml), in comparison with women with normal BMI (8.11± 1.52ng/ml), Conclusions: Insulin-like peptide 5 (INSL5) could play in a role in promoting insulin resistance (IR), Phosphodiesterase 9 (PDE9) is a regulator of energy, Phosphodiesterase 9 (PDE9) inhibition is associated with increase the occurrence of insulin resistance.